The sponge effect and carbon emission mitigation potentials of the global cement cycle - Zhi Cao (Nature Portfolio, 2020)
Cement plays a dual role in the carbon cycle like a sponge. Here, the authors employ a dynamic model to quantify such sponge effect and concluded that deep decarbonization of the global cement cycle will require radical technology advancements and widespread deployment of material efficiency measures.